Evaluating an Interspecific Helianthus annuus × Helianthus nuttallii Line for Use in Sunflower Breeding Program - Roumiana Dimova Vassilevska-Ivanova; Ira Stancheva; Maria Geneva; Zoya Tcekova (Turkish Journal of Agriculture: Food Science and Technology)
Interspecific cross was made between the common sunflower inbred line HA89 and an accession of wild Helianthus nuttallii (2n=2x=34) resistant to the most harmful disease complex and tolerant to drought and high temperature. The recombinant inbred line was a BC1F15 progeny. The most remarkable feature observed was the vigorous plant habit that manifests itself in measurable morphological characters such as increment plant height, stem diameter and diameter of the head. The line was non-branched (monocephalic) without anthocyanin pigmentation and possessed good agronomic characteristics. Along with the morphological and reproductive traits, some biochemical characteristics related to antioxidant activity were associated to wide hybridization. The overall characteristics of HA-Hnutt line make it a useful plant material for research on interspecific hybridization in Helianthus genus.